A workspace‐orientated needle‐guiding robot for 3T MRI‐guided transperineal prostate intervention: evaluation of in‐bore workspace and MRI compatibility. Issue 1 (10th April 2012) - Song, Sang‐Eun; Hata, Nobuhiko; Iordachita, Iulian; Fichtinger, Gabor; Tempany, Clare; Tokuda, Junichi
Abstract Background Magnetic resonance imaging (MRI)‐guided prostate interventions have been introduced to enhance the cancer detection. For accurate needle positioning, in‐bore‐operated robotic systems have been developed and optimal use of the confined in‐bore space become a critical engineering challenge. Methods As preliminary evaluation of our prostate intervention robot, we conducted a workspace design analysis, using a new evaluation method that we developed for in‐bore‐operated robots for transperineal prostate interventions, and an MRI compatibility study. Results The workspace analysis resulted in the effective workspace (VW) of 0.32, which is greater than that of our early prototype, despite the current robot being ca. 50% larger than the early prototype in sectional space. The MRI compatibility study resulted in < 15% signal:noise ratio (SNR) reduction. Conclusions The new workspace evaluation method quantifies the workspace utilization of the in‐bore‐operated robots for MRI‐guided transperineal prostate interventions, providing a useful tool for evaluation and new robot design. The robot creates insignificant electromagnetic noise during typical prostate imaging sequences. Copyright © 2012 John Wiley & Sons, Ltd.